2004
DOI: 10.1016/j.euje.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Native aortic valve vegetative endocarditis with Cunninghamella

Abstract: Cunninghamella bertholletiae is a rare Mucor species that is seldom the cause for endocarditis of prosthetic heart valves. It is even a more uncommon cause of endocarditis of native heart valves. We present a case of Cunninghamella endocarditis of a native aortic valve in an immuno-compromised patient, diagnosed from tissue culture obtained at the time of surgery. There have only been two other reported cases of native valve endocarditis with a Mucor species, and in those cases, the diagnoses were made post-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…In addition, these fungi have been implicated in central-venous-catheter-associated fungaemia (Chan-Tack et al, 2005), peritonitis in patients undergoing continuous ambulatory peritoneal dialysis (Branton et al, 1990;Fergie et al, 1992;Nakamura et al, 1989;Nannini et al, 2003;Nayak et al, 2007;Polo et al, 1989;Serna et al, 2003), pleuritis following implantation of drainage catheters (Kimura et al, 2009), endocarditis on native (Mehta et al, 2004;Mitchell et al, 2010) and artificial heart valves (Gubarev et al, 2007;Sanchez-Recalde et al, 1999), osteomyelitis (Chaudhuri et al, 1992;Eaton et al, 1994;Lopes et al, 1995;Meis et al, 1994;Wilkins et al, 2009), and paranasal fungal balls (Goodnight et al, 1993;Kirkpatrick et al, 1979;Lahiri et al, 2001;Robey et al, 2009). Many of these infections are associated with biofilm formation (Costerton et al, 1999;Hall-Stoodley et al, 2004;Loussert et al, 2010) and were reported to exhibit a chronic course (Eaton et al, 1994;Lahiri et al, 2001;Lopes et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these fungi have been implicated in central-venous-catheter-associated fungaemia (Chan-Tack et al, 2005), peritonitis in patients undergoing continuous ambulatory peritoneal dialysis (Branton et al, 1990;Fergie et al, 1992;Nakamura et al, 1989;Nannini et al, 2003;Nayak et al, 2007;Polo et al, 1989;Serna et al, 2003), pleuritis following implantation of drainage catheters (Kimura et al, 2009), endocarditis on native (Mehta et al, 2004;Mitchell et al, 2010) and artificial heart valves (Gubarev et al, 2007;Sanchez-Recalde et al, 1999), osteomyelitis (Chaudhuri et al, 1992;Eaton et al, 1994;Lopes et al, 1995;Meis et al, 1994;Wilkins et al, 2009), and paranasal fungal balls (Goodnight et al, 1993;Kirkpatrick et al, 1979;Lahiri et al, 2001;Robey et al, 2009). Many of these infections are associated with biofilm formation (Costerton et al, 1999;Hall-Stoodley et al, 2004;Loussert et al, 2010) and were reported to exhibit a chronic course (Eaton et al, 1994;Lahiri et al, 2001;Lopes et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…2). We identified three additional patients in whom dissemination was likely (164,211,286). All but one of the patients with disseminated infection caused by C. bertholletiae died of the infection (296).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although rarely diagnosed antemortem, invasion of the heart and/or pericardium is common in reported cases of disseminated C. bertholletiae infection, and it occurred in 62% of infections (n ϭ 13). After the lungs, the heart was the most common organ involved in disseminated infection (67,122,140,161,206,209,211,222,227,236,286,371). Among the patients with heart involvement, the lungs were also affected in 79% of cases (11/14 patients) ( Table 3).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations